The cultivation of immobilized chlorella vulgaris in different culture medium for biodiesel production - Nur Hanani, Rushan (2021)
Microalgae is known as an alternative source and promising feedstock for biodiesel production that can produce oil due to their simple unicellular structure and high photosynthetic efficiency. In this experiment, Chlorella vulgaris is selected as microalgae as this species is able to produce high oil for biodiesel processing. Immobilization is one of the harvesting methods employed in this study due to less energy consumed and ease of handling. Previously, the matric system which is sodium alginate (SA) was commonly used to entrap the microalgae in culturing process. However, SA has certain limitation such as bead disruption or bead dissolution that lead to the loss of microalgae cell. In addition, the required nutrient is one of the constrains that need to be overcome to enhance the production of oil. Therefore, the combination of matric system has been developed in this study in order to enhance the production of oil. In the present study, SA act s as a control whereas five different matric systems were combined with SA such as chitosan (SA+CT), carrageenan (SA+CR), gelatine (SA+GT), calcium alginate (SA+CA) and sodium carboxymethylcellulose (SA+CMC). The first objective in this study was to elucidate different culture medium of C. vulgaris by using Bold’s Basal Medium (BBM), Blue-Green Medium (BG11) and Jaworski’s medium (JM) while the second objective was to evaluate the oil production of immobilized C. vulgaris using different matric systems at different volumetric ratios of 0.3:1, 1:1 and 2:1 for biodiesel production. Besides, analysing the fatty acid methyl ester which extracted from freshwater microalgae was the third objective while determining kinetic and thermodynamic parameter were exhibited using reaction rate equation and Gibbs energy equation was the fourth objective in this study. The microalgae were first cultivated, harvested and extracted using solvent extraction method to produce oil, prior to use in the transesterification process using Gas chromatography mass spectrophotometer (GC-MS). Then, the fatty acid methyl ester extracted from C. vulgaris was analysed using GC-MS. Based on the results obtained, the best culture media was BBM which showed the highest oil yield which is 27.14% whereas the combination of SA+GT as a matric showed the highest oil yield with 44.29%. In this study, the main components of fatty acid methyl ester in the C. vulgaris of oil extracted from microalgae showed high potential for biodiesel production as it consisted of palmitic acid (C16:0), stearic acid (C18:0), oleic acid (C18:1), linoleic acid (C18:2) and linolenic acid (C18:3). The percentage of saturated fatty acid (C16:0 & C18:0) were higher than the unsaturated fatty acid (C18:1, C18:2 & C18:3). The kinetic study shows that the value of activation energy (Ea) for the oil extraction kinetics of microalgae biomass was calculated as 26.382 kJ/mol. Both enthalpy (ΔH) and entropy (ΔS) indicate positive value whereas the negative value of Gibbs energy (ΔG) indicates that this process is endothermic, irreversible and spontaneous. The research findings show that the BBM was more effective in culturing process and the applicability of the matric systems of SA+GT made a new structure that improve the oil production than using single matric. Furthermore, the similar fatty acid methyl ester (FAME) profile was showing a huge potential for biodiesel production.